2023
DOI: 10.3389/fmicb.2023.1097574
|View full text |Cite
|
Sign up to set email alerts
|

A scoring system based on novel biomarkers and clinical risk factors to predict invasive candidiasis in immunocompetent critically ill patients

Abstract: BackgroundDelayed diagnosis further increases the mortality of invasive candidiasis (IC) in intensive care unit (ICU) patients. This study aimed to develop and validate a score based on novel serological biomarkers and clinical risk factors for predicting IC in immunocompetent ICU patients.MethodsWe retrospectively collected clinical data and novel serological markers on admission to ICU. Multivariate logistic regression was used to identify the risk factors associated with IC, which were adopted to establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Li et al found that the novel biomarkers CAR, NLR, and PNI were significantly altered in patients with invasive candidiasis. These biomarkers were significantly associated with disease severity and prognosis of ICU patients [ 6 ]. PNI is a nutritional index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al found that the novel biomarkers CAR, NLR, and PNI were significantly altered in patients with invasive candidiasis. These biomarkers were significantly associated with disease severity and prognosis of ICU patients [ 6 ]. PNI is a nutritional index.…”
Section: Discussionmentioning
confidence: 99%
“…These markers are composed of two or more clinical laboratory indicators. The novel biomarker and their formulas are as follows; CAR = CRP (C-reactive protein) (mg/L) /albumin(g/L), NLR = neutrophil counts (10 9 /L) /lymphocyte counts(10 9 /L), PNI (Prognostic nutritional index) = 10 × albumin(g/L) + 5 × lymphocyte count (10 9 /L), PLR (platelet-to-lymphocyte ratio) = platelet counts (10 9 /L) /lymphocyte counts (10 9 /L), SII (systemic immune inflammation index) = platelet count (10 9 /L) × neutrophil count (10 9 /L)/lymphocyte count (10 9 /L) [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this issue of the European Journal of Clinical Investigation, Li et al 9 have proposed a clinical-laboratory prediction score for diagnosing IPA in an immunocompetent critically ill population. In the retrospective study by Li et al, 9 1841 immunocompetent patients admitted to ICU were randomly assigned to training and validation cohorts.…”
Section: E D I T O R I a L Editorial To 'A Score For Predicting Invas...mentioning
confidence: 99%
“…In this issue of the European Journal of Clinical Investigation, Li et al 9 have proposed a clinical-laboratory prediction score for diagnosing IPA in an immunocompetent critically ill population. In the retrospective study by Li et al, 9 1841 immunocompetent patients admitted to ICU were randomly assigned to training and validation cohorts. A prediction score was developed with host factors such as chronic obstructive pulmonary disease (COPD), continuous renal replacement therapy (CRRT), broad-spectrum antibiotics utilization and laboratory tests [i.e.…”
Section: E D I T O R I a L Editorial To 'A Score For Predicting Invas...mentioning
confidence: 99%
See 1 more Smart Citation